Hydrothermal alteration, contact metamorphism, and authigenesis in Ferrar Supergroup and Beacon Supergroup rocks, Carapace Nunatak, Allan Hills, and Coombs Hills, Victoria Land, Antarctica - Ballance, P.F.; Watters, W.A. (Royal Society Of New Zealand, 2002)
Permian-Triassic Beacon Supergroup (dominantly quartz-rich sandstones with coal) and Jurassic Ferrar Supergroup (mafic intrusives, extrusives, and phreatomagmatic clastic rocks), in the region studied, are separated by 20 m.y. of uplift, erosion, and nondeposition. Probable pre-Ferrar secondary minerals in Beacon rocks comprise overgrowths of quartz and K-feldspar followed by a cement of fine-grained sericitic mica and quartz. In Ferrar clastic rocks, some intrastratal dissolution of quartz and feldspar was followed by a cement of hydrothermal zeolite (heulandite/clinoptilolite-stilbite) which fills pores and replaces fine matrix and detrital mineral grains. Later overgrowths of plagioclase, quartz, and potash feldspar all replace zeolite. Finally, calcite replaces all previous mineral phases. This paragenesis occurs in Carapace Sandstone (Ferrar Supergroup), but Mawson Formation breccias (Ferrar) and some Beacon sandstones probably follow the same sequence, though less completely. Silica needed to form the late phases may have been derived from mineral conversions deeper in the stratigraphic pile or in underlying basement rocks (e.g., sodic plagioclase to laumontite), whereas silica released by conversion of heulandite to late calcite may have provided the quartz-chalcedony filling of vugs in Kirkpatrick Basalt. Pore-filling calcite cement in some Beacon sandstones may be pre-Ferrar, but a suitable Ca source is not known. Late replacement calcite may have utilised methane and CO2 from Beacon coals, and Ca from plagioclase and calcium zeolites in Ferrar rocks. Zeolite-facies burial metamorphism is indicated by laumontite, but its rarity constrains temperatures to around or below 210ﾰC, and there is no indication of a vertical temperature zonation. Thermal metamorphism adjacent to dikes and sills is generally minor, involving recrystallisation of matrix and loss of original fabric. Sandstone blocks within large dolerite intrusions have locally melted; tridymite and cristobalite probably formed at this time but inverted to quartz during cooling. Slow cooling of partial fusion melt produced spherulitic structures. Zeolite and calcite cements postdate thermal metamorphism. The main zeolite minerals are heulandite/clinoptilolite and stilbite, accompanied locally by one or more of laumontite, chabazite, analcime, and epistilbite. An open access copy of this article is available from the publishers website.